Relativer Energiemangel im Sport (REDs) - Petzoldt, T. (IAT, 2024)
Zusammenfassung des Originalartikels: Mountjoy, M., Ackerman, K. E., Bailey, D. M., Burke, L. M., Constantini, N., Hackney, A. C., Heikura, I. A., Melin, A., Pensgaard, A. M., Stellingwerff, T., Sundgot-Borgen, J. K., Klungland Torstveit, M., Uhrenholdt Jacobsen, A., Verhagen, E., Budgett, R., Engebretsen, L., & Erdener, U. (2023). 2023 International Olympic Committee`s (IOC) consensus statement on Relative Energy Deficiency in Sport (REDs). British Journal of Sports Medicine, 57(17), 1073-1097. 10.1136/bjsports-2023-106994